Merdeka Curriculum from The Students' Perspective: A Qualitative Study on Learning Perceptions and Experiences - Saputra, Muhammad Ari; Batubara, Romaito; Nasution, Ade Candra; Safitri, Rahma; Mardia, Nur Anisah; Lubis, Rohani; Pratama, Riski; Azizah, Nur (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2026)
This qualitative study investigates students’ perceptions and experiences regarding the implementation of the Merdeka Curriculum in Indonesian secondary schools. Using a phenomenological approach, the research involved semi-structured interviews with 12 high school students across one province, aiming to explore how students perceive and engage with the curriculum's core elements: flexibility, project-based learning, and formative assessment. Thematic analysis of the interview data revealed four central themes: (1) increased learning autonomy and flexibility, (2) challenges in managing self-directed learning, (3) enhanced engagement through contextual and collaborative learning, and (4) mixed clarity regarding assessment practices. While students appreciated the personalized and meaningful learning experiences afforded by the Merdeka Curriculum, many expressed a need for clearer guidance, structured support, and consistent feedback from teachers. The findings highlight both the transformative potential and the implementation challenges of the Merdeka Curriculum. This study recommends targeted teacher training, improved communication of learning goals and assessment standards, and ongoing support mechanisms to ensure students are equipped to succeed in a more autonomous learning environment.